(untitled) (Research, Society and Development, 2025)
A healthy and adequate diet is important from childhood, as it helps prevent various non-communicable diseases, such as cardiovascular diseases, obesity, and mineral and vitamin deficiencies. Children with Autism Spectrum Disorder may have restricted interests, including eating habits. This results in limited consumption of food groups, developing food refusal or selectivity, where they base their diet on visual issues, smell and texture, and not just taste, having preferences for certain foods, denying themselves to eat, try or get to know other foods, requiring treatment and the use of strategies to increase this consumption in a pleasurable and pressure-free way, respecting the child’s time and decision. The objective of the article is to present a study on food selectivity in children with Autism Spectrum Disorder, through a narrative review. The analysis of food selectivity in children with Autism Spectrum Disorder reveals the complexity of the interactions between food preferences, child development and health. Therefore, the importance of playful and educational approaches to encourage the exploration of different foods is noted, promoting not only the acceptance of a more varied diet, but also the development of sensory and social skills through the implementation of strategies that respect the rhythm and children’s needs to avoid frustrations and battles during mealtimes.